Scots Wiki – moving forward - Thomas, Sara (Septentrio Conference Series, 2021)
How do you recover after a crisis? This session will reflect on the work done by and with the sco.wiki community to recover and rebuild after the negative international press attention that surrounded the wiki in 2020. I’ll talk about on- and off- wiki community development, partnership development, the challenges that still face the project, and hopes for the future. I’ll also reflect on care in volunteer management, and why we should always remember that there are real people behind keyboards. As Scotland Programme Coordinator for Wikimedia UK, I’ve been involved in supporting the community post-crisis, and have been impressed and heartened by the volume of work which has taken place since sco.wiki hit the headlines. I’d like to take this opportunity to tell the story of a group of editors and Scots speakers who are determined that the wiki should survive, grow, and thrive. Abstract id. 11: In the lead-up to the launch of Abstract Wikipedia, a sufficient body of linguistic information, based on which the text within for a given language can be generated, must be in place so that different sets of functions, some working with concepts and others turning these into word sequences, can work together to produce something natural in that language. To achieve that information body's development requires more thorough consideration of a number of linguistic aspects sooner rather than later. This session will thus discuss aspects of language planning with respect to Wikidata lexicographical data and natural language generation, including the compositionality and manipulability of lexical units, the breadth and interconnectedness of units of meaning, and the treatment of variation among a language’s lects broadly construed. Special reference to the handling of each of these aspects for Bengali and those linguistic varieties often grouped with it will be presented.